PRODUCT INNOVATION AND QUALITY IN MUSLIM FASHION MSMES : CHALLENGES AND OPPORTUNITIES IN BANDUNG - Maria Merry Marianti; Katlea Fitriani; Ria Satyarini; Puteri Andika Sari (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
Bandung is part of the UNESCO Creative Cities Network in Indonesia, which is expected to become a world Muslim fashion center, but currently, its growth is threatened due to the entry of well-known brands and imported products, while Muslim fashion MSMEs in Bandung City are still far behind. This study aims to determine the level of product innovation and product quality produced by Muslim fashion MSMEs in Bandung City, as well as any matters related to product innovation and product quality that still need to be improved to increase the competitiveness of their businesses. The descriptive analysis method was used to analyze product quality and innovation in 100 Muslim fashion MSMEs in Bandung City, Indonesia. The results of this study found that the larger the business scale, the higher the level of product innovation; the quality level of small businesses is higher than the quality level of micro-businesses, but the quality level of medium enterprises is lower than the quality level of small businesses. The results of this research can be useful for developing product innovation models and product quality for the Muslim fashion industry.